Klasifikasi Penutupan Lahan Menggunakan Google Earth Engine dengan Metode Klasifikasi Terbimbing pada Wilayah Penajam Paser Utara - Muhammad Raiza Pratama; Dwiza Riana (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Abstract The district area is a priority area for industrial development and is one of the capital cities in Indonesia. from the development plan in the coastal area of North Penajam Paser Regency, it will affect land use from year to year as the industry develops in the area. Therefore, it is important to conduct research on the evaluation of land cover in the North Penajam Paser Regency area in order to determine the impact of the North Penajam Paser Regency spatial plan. One method for monitoring land cover change data is using remote sensing methods. The method used in this study uses a guided classification with the Classification and Regression Trees (CART) algorithm which is run through the google earth engine. The trend of changes in land cover that experienced an increase in the period of 2002, 2012, and 2020 was built up land, bush grass, open land. The trend of land cover changes that have decreased in the period of 2002, 2012, and 2022 is vegetation, water bodies, ponds, and rice fields. Keywords— North Penajam Paser Area, Land Cover, Google Earth Engine, CART